Multibeam bathymetry processed data (Atlas Hydrosweep DS 3 echo sounder entire dataset) of RV POLARSTERN during cruise PS146, Weddell Sea, Southern Ocean - Annie Lemire; Paula Allertseder; Miao Fan; Simon Dreutter; Boris Dorschel (PANGAEA, 2025)
Multibeam data were collected during RV Polarstern cruise PS146 (2024-12-24 to 2025-03-10). Multibeam sonar system was Atlas Hydrographic Hydrosweep DS 3 multibeam echo sounder. Data are processed with Caris HIPS, including sound velocity correction with SV data from CTDs and World Ocean Atlas 18 (https://www.ncei.noaa.gov/archive/accession/NCEI-WOA18), tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.